Vicente Lledó-Guillem, «The Making of Catalan Linguistic Identity in Medieval and Early Modern Times», Nova York, Palgrave MacMillan, 2018, 250 p. - Lloret, Albert (Caplletra. Revista Internacional de Filologia, 2019)
Ressenya sobre el llibre de Vicente Lledó-Guillem, The Making of Catalan Linguistic Identity in Medieval and Early Modern Times, Nova York, Palgrave MacMillan, 2018, 250 p., ISBN: 978-3-319-72080-7.